An evaporative cooling vest based on nanofiber aerogel and its preparation method and application

By developing nanofiber aerogel composite materials, the existing cooling vest cooling effect and insufficient rate have been solved, and efficient cooling effect has been achieved, which is suitable for high-temperature operating environments.

CN118456989BActive Publication Date: 2025-03-21WUYI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410429884.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2025-03-21
Estimated Expiration
2044-04-10

AI Technical Summary

Technical Problem

The existing water evaporative cooling vest has insufficient cooling effect and rate, which limits its application in high-temperature operating environments.

Method used

A nanofiber aerogel composite material was developed, including a polyacrylonitrile fiber aerogel layer and a waterproof and moisture-permeable nanofiber layer on both sides, prepared by electrospinning process.

Benefits of technology

This material has a high water absorption rate and good cooling rate and effect. It can achieve a cooling effect of 8 to 10°C in a high temperature environment above 35 degrees Celsius, and is suitable for high-temperature operating environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004785240810000011
    Figure HDA0004785240810000011
Patent Text Reader

Abstract

The present invention discloses an evaporative cooling vest based on nanofiber aerogel and a preparation method and application thereof, which are used in the technical field of electrostatic spinning nano-functional materials. The nanofiber aerogel composite material of the present invention comprises a polyacrylonitrile fiber aerogel layer and a waterproof and breathable nanofiber layer arranged on the upper and lower sides of the polyacrylonitrile fiber aerogel layer. The nanofiber aerogel composite material of the present invention is easy to use and operate, and only needs to be soaked in liquid water, and the water absorption rate is as high as 30 to 50 times, and the waterproof and breathable layers on both sides can prevent liquid water from contacting the skin, ensuring wearing comfort. After the composite material absorbs water, it quickly cools the human body in hot weather environments, and achieves a cooling effect of 8 to 10°C in a high temperature environment above 35 degrees Celsius. It has great application prospects in the field of preparing steam cooling vests and other clothing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrospinning nano functional materials, and relates to a nanofiber aerogel composite material and a preparation method and application thereof. Background Art

[0002] Cooling vests can absorb heat during the phase transition process of materials to reduce the surface temperature of human skin in hot climates, maintain a suitable temperature in the human microenvironment, effectively improve human comfort and work efficiency, and prevent heat stroke and shock. In actual use, cooling vests need to have the characteristics of simple operation, reusability, fast cooling speed, and strong effect. Water evaporation cooling vests have the characteristics of strong heat absorption and easy wear, which are suitable for cooling the human body in hot climates. At present, water evaporation cooling vests mostly use hydrophilic fibers or water-absorbing fibers as raw materials, and form three-dimensional fabrics through weaving, which can absorb a certain amount of liquid water; but because the fibers are relatively coarse and the specific surface area is low, the cooling rate and effect are limited. For example, an existing comfortable bionic cooling vest has a low water absorption rate, resulting in a weak cooling effect, which limits its application in the field of work clothing in high-temperature working environments such as traffic police uniforms, sanitation work clothes, and boiler work clothes.

[0003] Therefore, there is an urgent need to develop nanofiber aerogel composite materials with high water absorption rate and good cooling rate and effect to meet their application needs in the field of cooling vest clothing. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a nanofiber aerogel composite material, which has the characteristics of fine fiber diameter, large specific surface area, high water absorption rate, etc., can quickly absorb a large amount of heat, has a strong cooling effect and a fast speed.

[0005] The invention also provides a method for preparing the nanofiber aerogel composite material.

[0006] The present invention also provides an evaporative cooling vest based on nanofiber aerogel.

[0007] A first aspect of the present invention provides a nanofiber aerogel composite material, wherein the nanofiber aerogel composite material comprises a polyacrylonitrile fiber aerogel layer and waterproof and moisture-permeable nanofiber layers arranged on the upper and lower sides of the polyacrylonitrile fiber aerogel layer.

[0008] The nanofiber aerogel composite material according to the first aspect of the present invention has at least the following beneficial effects:

[0009] The nanofiber aerogel composite material in the present invention is composed of polyacrylonitrile nanofiber aerogel and nanofiber waterproof and breathable layers on the upper and lower sides. It has the characteristics of fine fiber diameter, large specific surface area, high water absorption rate, etc. Therefore, after absorbing water, the cooling vest can quickly absorb a large amount of heat, has a strong cooling effect and a fast speed, and effectively maintains a suitable temperature in the human body microenvironment.

[0010] Different from other nanofiber aerogel composite materials currently available, the nanofiber aerogel composite material of the present invention is easy to use and can be easily soaked in liquid water. The water absorption rate is as high as 30 to 50 times. Even if the human body exercises properly, it can effectively prevent liquid water from penetrating into the skin, ensuring the dryness of the human skin surface and improving wearing comfort. After the composite material of the present invention absorbs water, it can quickly cool the human body in hot weather and achieve a cooling effect of 8 to 10°C in a high temperature environment above 35 degrees Celsius.

[0011] According to some embodiments of the present invention, the thickness of the polyacrylonitrile fiber aerogel layer is 50 to 300 μm.

[0012] According to some embodiments of the present invention, the fiber diameter in the polyacrylonitrile fiber aerogel layer is 50 nm to 5 μm.

[0013] According to some embodiments of the present invention, the average aspect ratio of the fibers in the polyacrylonitrile fiber aerogel layer is 100 to 10,000.

[0014] According to some embodiments of the present invention, the thickness of the waterproof and moisture-permeable nanofiber layer on any one side is 20 to 100 μm.

[0015] A second aspect of the present invention provides a method for preparing a nanofiber aerogel composite material, the preparation method comprising the following steps:

[0016] S1, dissolving polyacrylonitrile in a first solvent to obtain a polyacrylonitrile spinning solution, and performing a first electrospinning to obtain a polyacrylonitrile nanofiber membrane;

[0017] S2, dispersing the polyacrylonitrile nanofiber membrane in a dispersant, and homogenizing it to obtain a polyacrylonitrile nanofiber suspension;

[0018] S3, freezing the polyacrylonitrile nanofiber suspension at low temperature, and then vacuum drying to obtain a polyacrylonitrile nanofiber aerogel layer;

[0019] S4, dissolving the hydrophobic polymer in a second solvent to obtain a hydrophobic polymer spinning solution, performing a second electrospinning on the polyacrylonitrile nanofiber aerogel layer to obtain a waterproof and moisture-permeable nanofiber layer, and obtaining a nanofiber aerogel composite material.

[0020] The preparation method according to the second aspect of the present invention has at least the following beneficial effects:

[0021] The preparation method of the nanofiber aerogel composite material of the present invention adopts the electrospinning process to prepare the polyacrylonitrile nanofiber membrane with uniform diameter, good mechanical strength and softness, and can effectively protect the body from the external environment. Prepared by freeze-vacuum drying, a porous and light aerogel structure is formed, which has excellent thermal insulation and air permeability, can effectively reduce the temperature of the back and improve wearing comfort.

[0022] The preparation method of the present invention can prepare nanofiber membranes and nanofiber layers with uniform diameters by using electrospinning technology, which have nano-level fine structures and high specific surface areas, and are conducive to improving the performance of the material. The water crystals in the suspension are frozen into ice crystals by freezing, and the water is evaporated under vacuum conditions to form a porous and light aerogel structure. This preparation method is simple and easy to operate and has strong controllability. By preparing waterproof and breathable nanofiber layers on both sides of the aerogel, the waterproofness of the vest is guaranteed, and good breathability is maintained, effectively preventing the vest from feeling hot and wet during exercise.

[0023] According to some embodiments of the present invention, in step S1, the mass fraction of polyacrylonitrile in the polyacrylonitrile spinning solution is 8-30%.

[0024] According to some embodiments of the present invention, in step S1, the first solvent is selected from at least one of NNN dimethylformamide, NNN dimethylacetamide, acetone and dimethyl sulfoxide.

[0025] According to some embodiments of the present invention, in step S1, the process parameters of the first electrospinning include: a spinning voltage of 10 to 40 kV, a drum speed of 200-800 rpm, a solution infusion rate of 1 to 6 mL / h, a receiving distance of 10 to 40 cm, and a spinning time of 1 to 10 h.

[0026] According to some embodiments of the present invention, in step S2, the dispersant is selected from at least one of aqueous polyurethane emulsion, sodium polyacrylate, polyvinyl pyrrolidone, sodium carboxymethyl cellulose and hydroxypropyl methyl cellulose.

[0027] Preferably, in step S2, the dispersant is an aqueous polyurethane emulsion.

[0028] According to some embodiments of the present invention, in step S2, the concentration of the dispersant is 0.1-10%.

[0029] According to some embodiments of the present invention, in step S2, the mass fraction of nanofibers in the polyacrylonitrile nanofiber suspension is 0.5-30%.

[0030] According to some embodiments of the present invention, in step S2, the homogenization process includes high-speed dispersing cutting.

[0031] According to some embodiments of the present invention, the process parameters of the high-speed dispersive cutting include: a homogenizing shearing speed of 100 to 20,000 rpm, and a homogenizing shearing time of 10 to 120 min.

[0032] According to some embodiments of the present invention, in step S3, the low-temperature freezing temperature is -100 to -30°C.

[0033] According to some embodiments of the present invention, in step S3, the low-temperature freezing time is 1 to 10 hours.

[0034] According to some embodiments of the present invention, in step S3, the vacuum drying time is 1 to 48 hours.

[0035] According to some embodiments of the present invention, in step S4, the mass fraction of the hydrophobic polymer in the hydrophobic polymer spinning solution is 1-20%.

[0036] According to some embodiments of the present invention, in step S4, the hydrophobic polymer is selected from at least one of polystyrene, polyvinylidene fluoride, fluorinated acrylic acid, fluorinated polyethylene and fluorinated polyurethane.

[0037] According to some embodiments of the present invention, in step S4, the second solvent is selected from at least one of dimethylformamide, dimethylacetamide, dichloromethane and methylpyrrolidone.

[0038] According to some embodiments of the present invention, in step S4, the process parameters of the second electrospinning include: a voltage of 1 to 40 kV, a receiving distance of 10 to 50 cm, and a liquid supply rate of the spinning solution of 0.5 to 5 mL / h.

[0039] A third aspect of the present invention provides use of the above-mentioned nanofiber aerogel composite material and / or the nanofiber aerogel composite material obtained by the above-mentioned preparation method in the preparation of a cooling vest.

[0040] The first aspect of the present invention provides an evaporative cooling vest based on nanofiber aerogel, the fabric of the evaporative cooling vest comprises the above-mentioned nanofiber aerogel composite material and / or the nanofiber aerogel composite material obtained by the above-mentioned preparation method.

[0041] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0043] Figure 1 Schematic diagram of the structure of the nanofiber aerogel composite material in an embodiment of the present invention, wherein 1 is a waterproof and moisture permeable nanofiber layer, 2 is a polyacrylonitrile fiber aerogel layer, and 3 is a waterproof and moisture permeable nanofiber layer. DETAILED DESCRIPTION

[0044] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0045] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0046] It should be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the technical solution of the present invention are shown in the accompanying drawings, while other details that are not closely related to the present invention are omitted. In addition, it should be noted that the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0047] Example 1

[0048] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0049] The first step: prepare a 15% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 40 kV, the drum speed is 200 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 10 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 60 μm.

[0050] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 3%) in 2% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 1000 rpm for 20 min. The average fiber diameter in the resulting suspension is 500 nm and the average aspect ratio of the fiber is 1000.

[0051] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 2 hours, and the vacuum drying time is 20 hours to obtain polyacrylonitrile nanofiber aerogel.

[0052] Step 4: Use NN dimethylacetamide as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 30 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 12 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 20 μm.

[0053] The final prepared nanofiber aerogel has a water absorption rate of 35 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0054] Example 2

[0055] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0056] The first step: prepare a polyacrylonitrile solution with a mass fraction of 18% using NN dimethylformamide as solvent, and prepare a nanofiber membrane on a spunbond cloth by an electrospinning method. The spinning voltage is 20 kV, the drum speed is 300 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 15 cm, the spinning time is 1.5 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0057] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 2.5%) in 2% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine. The speed of the homogenizing shearing machine is 1000 rpm and the action time is 30 minutes. The average diameter of the fibers in the resulting suspension is 300 nm and the average aspect ratio of the fibers is 800.

[0058] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -90°C, the freezing time is 1 hour, and the vacuum drying time is 15 hours to obtain polyacrylonitrile nanofiber aerogel.

[0059] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 350 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 12 cm, the spinning time is 1.5 h, and the thickness of the obtained nanofiber membrane is 40 μm.

[0060] The final prepared nanofiber aerogel has a water absorption rate of 38 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 11kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0061] Example 3

[0062] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0063] The first step: prepare a 23% polyacrylonitrile solution with NN dimethylacetamide as solvent, and prepare a nanofiber membrane on a spunbond cloth by electrospinning. The spinning voltage is 10 kV, the drum speed is 300 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 10 cm, the spinning time is 1.5 h, and the thickness of the obtained nanofiber membrane is 70 μm.

[0064] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 2000 rpm for 30 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 800.

[0065] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -100°C, the freezing time is 1 hour, and the vacuum drying time is 15 hours to obtain polyacrylonitrile nanofiber aerogel.

[0066] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 40 μm.

[0067] The final prepared nanofiber aerogel has a water absorption rate of 40 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 10°C in a high temperature environment above 35 degrees Celsius.

[0068] Example 4

[0069] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0070] The first step: prepare a 20% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 20 kV, the drum speed is 500 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 20 cm, the spinning time is 2 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0071] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction 5%) in 4% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 3000 rpm for 40 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 700.

[0072] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 1 hour, and the vacuum drying time is 18 hours to obtain polyacrylonitrile nanofiber aerogel.

[0073] Step 4: Use NN dimethylacetamide as solvent to prepare a 20% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 40 μm.

[0074] The final prepared nanofiber aerogel has a water absorption rate of 45 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 12kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0075] Example 5

[0076] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0077] The first step: prepare a 20% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 20 kV, the drum speed is 500 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 20 cm, the spinning time is 2 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0078] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 2000 rpm for 30 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 800.

[0079] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 1 hour, and the vacuum drying time is 18 hours to obtain polyacrylonitrile nanofiber aerogel.

[0080] Step 4: Use NN dimethylacetamide as solvent to prepare a 20% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 40 μm.

[0081] The final prepared nanofiber aerogel has a water absorption rate of 46 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 11kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0082] Example 6

[0083] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0084] The first step: prepare a polyacrylonitrile solution with a mass fraction of 18% using NN dimethylformamide as solvent, and prepare a nanofiber membrane on a spunbond cloth by an electrospinning method. The spinning voltage is 20 kV, the drum speed is 300 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 15 cm, the spinning time is 1.5 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0085] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 5%) in 4% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 4000 rpm for 20 min. The average fiber diameter in the resulting suspension is 800 nm and the average aspect ratio of the fiber is 1000.

[0086] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -60°C, the freezing time is 2 hours, and the vacuum drying time is 28 hours to obtain polyacrylonitrile nanofiber aerogel.

[0087] Step 4: Use NN dimethylacetamide as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 16 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 60 μm.

[0088] The final prepared nanofiber aerogel has a water absorption rate of 48 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 12kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0089] Example 7

[0090] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0091] The first step: prepare a 20% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 2 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0092] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 6%) in 2% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 3500 rpm for 30 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1500.

[0093] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -50°C, the freezing time is 2h, and the vacuum drying time is 25h to obtain polyacrylonitrile nanofiber aerogel.

[0094] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion speed is 1.5 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0095] The final prepared nanofiber aerogel has a water absorption rate of 50 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 12kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0096] Example 8

[0097] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0098] The first step: prepare a 10% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 30 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 30 cm, the spinning time is 1.5 h, and the thickness of the obtained nanofiber membrane is 150 μm.

[0099] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 5%) in 4% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 3000 rpm for 40 min. The average fiber diameter in the resulting suspension is 750 nm and the average aspect ratio of the fiber is 1200.

[0100] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -50°C, the freezing time is 2.5 hours, and the vacuum drying time is 20 hours to obtain polyacrylonitrile nanofiber aerogel.

[0101] Step 4: Use NN dimethylacetamide as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 30 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 28 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0102] The final prepared nanofiber aerogel has a water absorption rate of 47 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 11kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0103] Example 9

[0104] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0105] The first step: prepare a 15% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 30 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 30 cm, the spinning time is 1.5 h, and the thickness of the obtained nanofiber membrane is 150 μm.

[0106] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 6%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 3000 rpm for 50 min. The average fiber diameter in the resulting suspension is 800 nm and the average aspect ratio of the fiber is 1500.

[0107] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -50°C, the freezing time is 2 hours, and the vacuum drying time is 25 hours to obtain polyacrylonitrile nanofiber aerogel.

[0108] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion speed is 1.5 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0109] The final prepared nanofiber aerogel has a water absorption rate of 45 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0110] Example 10

[0111] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0112] The first step: prepare a polyacrylonitrile solution with a mass fraction of 18% using NN dimethylformamide as solvent, and prepare a nanofiber membrane on a spunbond cloth by an electrospinning method. The spinning voltage is 20 kV, the drum speed is 300 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 15 cm, the spinning time is 1.5 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0113] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 6%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 3500 rpm for 40 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1500.

[0114] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -60°C, the freezing time is 2 hours, and the vacuum drying time is 20 hours to obtain polyacrylonitrile nanofiber aerogel.

[0115] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion speed is 1.5 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0116] The final prepared nanofiber aerogel has a water absorption rate of 43 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0117] Embodiment 11

[0118] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0119] The first step: prepare a 20% polyacrylonitrile solution with NN dimethylacetamide as solvent, and prepare a nanofiber membrane on a spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 300 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 15 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0120] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 4% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 3000 rpm for 30 min. The average fiber diameter in the resulting suspension is 550 nm and the average aspect ratio of the fiber is 1000.

[0121] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -50°C, the freezing time is 2 hours, and the vacuum drying time is 25 hours to obtain polyacrylonitrile nanofiber aerogel.

[0122] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion speed is 1.5 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0123] The final prepared nanofiber aerogel has a water absorption rate of 46 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0124] Example 12

[0125] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0126] The first step: prepare a 15% polyacrylonitrile solution with NN dimethylacetamide as solvent, and prepare a nanofiber membrane on a spunbond cloth by electrospinning. The spinning voltage is 20 kV, the drum speed is 500 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 18 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0127] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 7%) in 4% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 4000 rpm for 30 min. The average fiber diameter in the resulting suspension is 650 nm and the average aspect ratio of the fiber is 1000.

[0128] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 2 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0129] Step 4: Use NN dimethylformamide as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 10 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0130] The final prepared nanofiber aerogel has a water absorption rate of 48 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0131] Embodiment 13

[0132] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0133] The first step: prepare a 20% polyacrylonitrile solution with NN dimethylacetamide as solvent, and prepare a nanofiber membrane on a spunbond cloth by electrospinning. The spinning voltage is 24 kV, the drum speed is 500 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 18 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0134] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 7%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 5000 rpm for 40 min. The average fiber diameter in the resulting suspension is 800 nm and the average aspect ratio of the fiber is 1100.

[0135] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 2.5 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0136] Step 4: Use NN dimethylformamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 30 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0137] The final prepared nanofiber aerogel has a water absorption rate of 38 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 10°C in a high temperature environment above 35 degrees Celsius.

[0138] Embodiment 14

[0139] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0140] The first step: prepare a 10% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 18 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0141] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 6%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 4500 rpm for 40 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1300.

[0142] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 2 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0143] Step 4: Use NN dimethylacetamide as solvent to prepare a 13% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 70 μm.

[0144] The final prepared nanofiber aerogel has a water absorption rate of 36 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 12kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0145] Embodiment 15

[0146] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0147] The first step: prepare a 15% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 35 kV, the drum speed is 600 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 18 cm, the spinning time is 5 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0148] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 6%) in 6% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 4000 rpm for 45 min. The average fiber diameter in the resulting suspension is 750 nm and the average aspect ratio of the fiber is 1400.

[0149] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 3 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0150] Step 4: Use NN dimethylacetamide as solvent to prepare a 20% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 40 μm.

[0151] The final prepared nanofiber aerogel has a water absorption rate of 35 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0152] Example 16

[0153] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0154] The first step: prepare a 20% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 30 kV, the drum speed is 500 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 15 cm, the spinning time is 5 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0155] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 4% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 6000 rpm for 30 min. The average fiber diameter in the resulting suspension is 800 nm and the average aspect ratio of the fiber is 1600.

[0156] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 4 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0157] Step 4: Use NN dimethylformamide as solvent to prepare a 16% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 24 kV, the drum speed is 400 rpm, the solution infusion speed is 1 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 50 μm.

[0158] The final prepared nanofiber aerogel has a water absorption rate of 36 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 12kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0159] Embodiment 17

[0160] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0161] The first step: prepare a 15% polyacrylonitrile solution with NN dimethylformamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 10 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 70 μm.

[0162] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 6%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7500 rpm for 40 min. The average fiber diameter in the resulting suspension is 850 nm and the average aspect ratio of the fiber is 1500.

[0163] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 4 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0164] Step 4: Use NN dimethylacetamide as solvent to prepare a 20% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 40 μm.

[0165] The final prepared nanofiber aerogel has a water absorption rate of 38 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 11kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0166] Embodiment 18

[0167] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0168] The first step: prepare a 10% polyacrylonitrile solution with NN dimethylacetamide as solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 10 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 60 μm.

[0169] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 8% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7000 rpm for 40 min. The average fiber diameter in the resulting suspension is 800 nm and the average aspect ratio of the fiber is 1300.

[0170] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 3 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0171] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 15 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 60 μm.

[0172] The final prepared nanofiber aerogel has a water absorption rate of 40 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 12kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0173] Embodiment 19

[0174] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0175] The first step: prepare a 17% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 20 kV, the drum speed is 450 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 25 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 70 μm.

[0176] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 3%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 6500 rpm for 35 min. The average fiber diameter in the resulting suspension is 1000 nm and the average aspect ratio of the fiber is 1000.

[0177] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 4 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0178] Step 4: Use dichloromethane as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 15 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 10 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 70 μm.

[0179] The final prepared nanofiber aerogel has a water absorption rate of 42 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 11kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0180] Embodiment 20

[0181] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0182] Step 1: Prepare a 15% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 450 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 20 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0183] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 3%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 6000 rpm for 35 min. The average fiber diameter in the resulting suspension is 800 nm and the average aspect ratio of the fiber is 1400.

[0184] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 3 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0185] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 15 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 60 μm.

[0186] The final prepared nanofiber aerogel has a water absorption rate of 45 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 12kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0187] Embodiment 21

[0188] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0189] The first step: prepare a 13% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 23 kV, the drum speed is 420 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 18 cm, the spinning time is 5 h, and the thickness of the obtained nanofiber membrane is 90 μm.

[0190] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 5%) in 6% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 6000 rpm for 35 min. The average fiber diameter in the resulting suspension is 800 nm and the average aspect ratio of the fiber is 1400.

[0191] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -90°C, the freezing time is 2 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0192] Step 4: Use dichloromethane as solvent to prepare a 13% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0193] The final prepared nanofiber aerogel has a water absorption rate of 48 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 11kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 10°C in a high temperature environment above 35 degrees Celsius.

[0194] Embodiment 22

[0195] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0196] The first step: prepare a 10% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 30 kV, the drum speed is 600 rpm, the solution infusion rate is 1.5 mL / h, the receiving distance is 15 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 90 μm.

[0197] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 10%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 8000 rpm for 50 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1400.

[0198] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 4 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0199] Step 4: Use NN dimethylacetamide as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 45 μm.

[0200] The final prepared nanofiber aerogel has a water absorption rate of 46 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 12kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0201] Embodiment 23

[0202] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0203] The first step: prepare a 15% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 30 kV, the drum speed is 500 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0204] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 6% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 8000 rpm for 30 min. The average fiber diameter in the resulting suspension is 900 nm and the average aspect ratio of the fiber is 1200.

[0205] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -50°C, the freezing time is 6 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0206] Step 4: Use dichloromethane as solvent to prepare a 12% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 16 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 10 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 40 μm.

[0207] The final prepared nanofiber aerogel has a water absorption rate of 42 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0208] Embodiment 24

[0209] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0210] The first step: prepare a 13% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 15 kV, the drum speed is 600 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 20 cm, the spinning time is 5 h, and the thickness of the obtained nanofiber membrane is 110 μm.

[0211] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 5%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 8000 rpm for 30 min. The average fiber diameter in the resulting suspension is 900 nm and the average aspect ratio of the fiber is 1200.

[0212] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 3 hours, and the vacuum drying time is 25 hours to obtain polyacrylonitrile nanofiber aerogel.

[0213] Step 4: Use dichloromethane as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 60 μm.

[0214] The final prepared nanofiber aerogel has a water absorption rate of 41 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0215] Embodiment 25

[0216] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0217] The first step: prepare a 14% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 30 kV, the drum speed is 650 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 15 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 120 μm.

[0218] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 13%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 8000 rpm for 30 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1400.

[0219] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -90°C, the freezing time is 2 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0220] Step 4: Use NN dimethylacetamide as solvent to prepare a 13% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 30 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 60 μm.

[0221] The final prepared nanofiber aerogel has a water absorption rate of 42 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0222] Embodiment 26

[0223] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0224] The first step: prepare a 15% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 20 kV, the drum speed is 200 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 15 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 140 μm.

[0225] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 15%) in 2% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 8000 rpm for 30 min. The average fiber diameter in the resulting suspension is 900 nm and the average aspect ratio of the fiber is 1200.

[0226] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -90°C, the freezing time is 2 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0227] Step 4: Use dichloromethane as solvent to prepare a 12% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 35 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0228] The final prepared nanofiber aerogel has a water absorption rate of 45 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0229] Embodiment 27

[0230] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0231] The first step: prepare a 13% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 18 kV, the drum speed is 450 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 120 μm.

[0232] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 15%) in 2% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 8000 rpm for 30 min. The average fiber diameter in the resulting suspension is 900 nm and the average aspect ratio of the fiber is 1200.

[0233] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -90°C, the freezing time is 2 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0234] Step 4: Use dichloromethane as solvent to prepare a 13% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0235] The final prepared nanofiber aerogel has a water absorption rate of 48 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0236] Embodiment 28

[0237] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0238] The first step: prepare a 17% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 20 kV, the drum speed is 450 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 25 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 70 μm.

[0239] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 3%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 6500 rpm for 35 min. The average fiber diameter in the resulting suspension is 1000 nm and the average aspect ratio of the fiber is 1000.

[0240] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -60°C, the freezing time is 4 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0241] Step 4: Use dichloromethane as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 30 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0242] The final prepared nanofiber aerogel has a water absorption rate of 48 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 9kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0243] Embodiment 29

[0244] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0245] The first step: prepare a 15% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 20 kV, the drum speed is 550 rpm, the solution infusion rate is 2.5 mL / h, the receiving distance is 25 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0246] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 15%) in 2% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 8000 rpm for 30 min. The average fiber diameter in the resulting suspension is 900 nm and the average aspect ratio of the fiber is 1200.

[0247] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 3 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0248] Step 4: Use dichloromethane as solvent to prepare a 12% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 35 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0249] The final prepared nanofiber aerogel has a water absorption rate of 46 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0250] Embodiment 30

[0251] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0252] The first step: prepare a 10% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 22 kV, the drum speed is 550 rpm, the solution infusion rate is 2.2 mL / h, the receiving distance is 26 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 90 μm.

[0253] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 10%) in 2.5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine. The speed of the homogenizing shearing machine is 6500 rpm and the action time is 40 minutes. The average diameter of the fibers in the obtained suspension is 560nm and the average aspect ratio of the fibers is 1500.

[0254] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 2 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0255] Step 4: Prepare a 14% polyvinylidene fluoride solution with methyl pyrrolidone as solvent, and prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel by electrospinning. The nanofiber waterproof and breathable layer is prepared with a spinning voltage of 30 kV, a drum speed of 400 rpm, a solution infusion rate of 2.5 mL / h, a receiving distance of 15 cm, a spinning time of 1 h, and a thickness of the obtained nanofiber membrane of 80 μm.

[0256] The final prepared nanofiber aerogel has a water absorption rate of 43 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0257] Embodiment 31

[0258] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0259] The first step: prepare a 14% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 600 rpm, the solution infusion rate is 1.2 mL / h, the receiving distance is 20 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0260] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 8%) in 2% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine. The speed of the homogenizing shearing machine is 6000 rpm and the action time is 30 minutes. The average diameter of the fibers in the obtained suspension is 660nm and the average aspect ratio of the fibers is 2000.

[0261] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 2.5 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0262] Step 4: Use methyl pyrrolidone as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 27 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 10 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 65 μm.

[0263] The final prepared nanofiber aerogel has a water absorption rate of 45 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0264] Embodiment 32

[0265] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0266] The first step: prepare a 13% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 27 kV, the drum speed is 800 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 10 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 110 μm.

[0267] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 4% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 5500 rpm for 35 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1500.

[0268] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -65°C, the freezing time is 4 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0269] Step 4: Use dichloromethane as solvent to prepare a 12% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0270] The final prepared nanofiber aerogel has a water absorption rate of 48 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0271] Embodiment 33

[0272] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0273] The first step: prepare a 14% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 600 rpm, the solution infusion rate is 1.2 mL / h, the receiving distance is 20 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0274] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 5500 rpm for 35 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1500.

[0275] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -65°C, the freezing time is 4 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0276] Step 4: Use dichloromethane as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 15 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 50 μm.

[0277] The final prepared nanofiber aerogel has a water absorption rate of 48 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0278] Embodiment 34

[0279] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0280] The first step: prepare a 20% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 600 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 150 μm.

[0281] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 6%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7600 rpm for 45 min. The average fiber diameter in the resulting suspension is 750 nm and the average aspect ratio of the fiber is 1600.

[0282] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -55°C, the freezing time is 3 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0283] Step 4: Use dichloromethane as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 26 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 25 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 60 μm.

[0284] The final prepared nanofiber aerogel has a water absorption rate of 45 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0285] Embodiment 35

[0286] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0287] Step 1: Prepare a 15% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 23 kV, the drum speed is 500 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 25 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 120 μm.

[0288] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 7%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7800 rpm for 40 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1400.

[0289] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -70°C, the freezing time is 2 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0290] Step 4: Use methyl pyrrolidone as solvent to prepare a polyvinylidene fluoride solution with a mass fraction of 11%, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 65 μm.

[0291] The final prepared nanofiber aerogel has a water absorption rate of 49 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0292] Embodiment 36

[0293] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0294] Step 1: Prepare a 17% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 26 kV, the drum speed is 570 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 24 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 100 μm.

[0295] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 8%) in 2% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7600 rpm for 45 min. The average fiber diameter in the resulting suspension is 700 nm and the average aspect ratio of the fiber is 1400.

[0296] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -90°C, the freezing time is 2h, and the vacuum drying time is 32h to obtain polyacrylonitrile nanofiber aerogel.

[0297] Step 4: Prepare a 14% polyvinylidene fluoride solution with methyl pyrrolidone as solvent, and prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel by electrospinning. The nanofiber waterproof and breathable layer is prepared with a spinning voltage of 15 kV, a drum speed of 400 rpm, a solution infusion rate of 2 mL / h, a receiving distance of 20 cm, a spinning time of 1 h, and a thickness of the obtained nanofiber membrane of 80 μm.

[0298] The final prepared nanofiber aerogel has a water absorption rate of 50 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 9kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 10°C in a high temperature environment above 35 degrees Celsius.

[0299] Embodiment 37

[0300] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0301] The first step: prepare a 13% polyacrylonitrile solution with acetone as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 20 kV, the drum speed is 550 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 20 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 130 μm.

[0302] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 7%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7500 rpm for 40 min. The average fiber diameter in the resulting suspension is 750 nm and the average aspect ratio of the fiber is 1500.

[0303] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 3 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0304] Step 4: Use methyl pyrrolidone as solvent to prepare a 15% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion speed is 3 mL / h, the receiving distance is 25 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 90 μm.

[0305] The final prepared nanofiber aerogel has a water absorption rate of 38 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve an 8°C cooling effect in a high temperature environment above 35 degrees Celsius.

[0306] Embodiment 38

[0307] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0308] The first step: prepare a polyacrylonitrile solution with a mass fraction of 18% with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 23 kV, the drum speed is 760 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 24 cm, the spinning time is 5 h, and the thickness of the obtained nanofiber membrane is 150 μm.

[0309] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 6%) in 4% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7000 rpm for 40 min. The average fiber diameter in the resulting suspension is 750 nm and the average aspect ratio of the fiber is 1500.

[0310] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -80°C, the freezing time is 2 hours, and the vacuum drying time is 30 hours to obtain polyacrylonitrile nanofiber aerogel.

[0311] Step 4: Use dimethylacetamide as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 20 kV, the drum speed is 400 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 70 μm.

[0312] The final prepared nanofiber aerogel has a water absorption rate of 36 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 8kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0313] Embodiment 39

[0314] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0315] The first step: prepare a 16% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 25 kV, the drum speed is 750 rpm, the solution infusion rate is 3 mL / h, the receiving distance is 27 cm, the spinning time is 3 h, and the thickness of the obtained nanofiber membrane is 130 μm.

[0316] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 4%) in 3% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7600 rpm for 45 min. The average fiber diameter in the resulting suspension is 780 nm and the average aspect ratio of the fiber is 900.

[0317] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -85°C, the freezing time is 3 hours, and the vacuum drying time is 32 hours to obtain polyacrylonitrile nanofiber aerogel.

[0318] Step 4: Use dimethylacetamide as solvent to prepare 8% polyvinylidene fluoride solution, and use electrospinning method to prepare waterproof and breathable nanofiber layer on both sides of polyacrylonitrile nanofiber aerogel to prepare nanofiber waterproof and breathable layer. The spinning voltage is 24kV, the drum speed is 400rpm, the solution infusion speed is 2mL / h, the receiving distance is 24cm, the spinning time is 1h, and the thickness of the obtained nanofiber membrane is 75μm.

[0319] The final prepared nanofiber aerogel has a water absorption rate of 38 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 9kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 10°C in a high temperature environment above 35 degrees Celsius.

[0320] Embodiment 40

[0321] A method for preparing a nanofiber aerogel composite material, comprising the following specific steps:

[0322] The first step: prepare a 13% polyacrylonitrile solution with dimethyl sulfoxide as the solvent, and prepare the nanofiber membrane on the spunbond cloth by electrospinning. The spinning voltage is 30 kV, the drum speed is 550 rpm, the solution infusion rate is 2 mL / h, the receiving distance is 23 cm, the spinning time is 4 h, and the thickness of the obtained nanofiber membrane is 120 μm.

[0323] Step 2: Disperse polyacrylonitrile nanofibers (mass fraction is 9%) in 5% aqueous polyurethane emulsion and shear them with a homogenizing shearing machine at a speed of 7500 rpm for 40 min. The average fiber diameter in the resulting suspension is 760 nm and the average aspect ratio of the fiber is 950.

[0324] Step 3: freeze-dry the suspension, the temperature of the ultra-low temperature refrigerator is -85°C, the freezing time is 2 hours, and the vacuum drying time is 35 hours to obtain polyacrylonitrile nanofiber aerogel.

[0325] Step 4: Use methyl pyrrolidone as solvent to prepare a 10% mass fraction of polyvinylidene fluoride solution, and use the electrospinning method to prepare a waterproof and breathable nanofiber layer on both sides of the polyacrylonitrile nanofiber aerogel to prepare a nanofiber waterproof and breathable layer. The spinning voltage is 25 kV, the drum speed is 400 rpm, the solution infusion rate is 1 mL / h, the receiving distance is 20 cm, the spinning time is 1 h, and the thickness of the obtained nanofiber membrane is 80 μm.

[0326] The final prepared nanofiber aerogel has a water absorption rate of 36 times in liquid water, and the water pressure resistance of the waterproof and breathable membranes on both sides is 10kPa. It can quickly cool down the human body in hot weather and achieve a cooling effect of 9°C in a high temperature environment above 35 degrees Celsius.

[0327] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A nanofiber aerogel composite material, characterized in that: The nanofiber aerogel composite material comprises a polyacrylonitrile fiber aerogel layer and a waterproof and moisture-permeable nanofiber layer disposed on the upper and lower sides of the polyacrylonitrile fiber aerogel layer; The thickness of the polyacrylonitrile fiber aerogel layer is 50 to 300 μm; The fiber diameter in the polyacrylonitrile fiber aerogel layer is 50nm to 5μm; The average aspect ratio of the fibers in the polyacrylonitrile fiber aerogel layer is 100 to 10000; The method for preparing the nanofiber aerogel composite material comprises the following steps: S1, dissolving polyacrylonitrile in a first solvent to obtain a polyacrylonitrile spinning solution, and performing a first electrospinning to obtain a polyacrylonitrile nanofiber membrane; S2, dispersing the polyacrylonitrile nanofiber membrane in a dispersant, and homogenizing it to obtain a polyacrylonitrile nanofiber suspension; S3, freezing the polyacrylonitrile nanofiber suspension at low temperature, and then vacuum drying to obtain a polyacrylonitrile nanofiber aerogel layer; S4, dissolving the hydrophobic polymer in a second solvent to obtain a hydrophobic polymer spinning solution, performing a second electrospinning on the polyacrylonitrile nanofiber aerogel layer to obtain a waterproof and moisture-permeable nanofiber layer, and obtaining a nanofiber aerogel composite material; Wherein, in step S2, the dispersant is selected from at least one of aqueous polyurethane emulsion, sodium polyacrylate, polyvinyl pyrrolidone, sodium carboxymethyl cellulose and hydroxypropyl methyl cellulose.

2. The nanofiber aerogel composite material according to claim 1, characterized in that: The thickness of the waterproof and moisture-permeable nanofiber layer on either side is 20 to 100 μm.

3. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S1, the mass fraction of polyacrylonitrile in the polyacrylonitrile spinning solution is 8-30%.

4. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S1, the first solvent is selected from at least one of N-N-dimethylformamide, N-N-dimethylacetamide, acetone and dimethyl sulfoxide.

5. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S1, the process parameters of the first electrospinning include: spinning voltage of 10-40 kV, drum speed of 200-800 rpm, solution infusion speed of 1-6 mL / h, receiving distance of 10-40 cm, and spinning time of 1-10 h.

6. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S2, the concentration of the dispersant is 0.1-10%.

7. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S2, the mass fraction of nanofibers in the polyacrylonitrile nanofiber suspension is 0.5-30%.

8. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S2, the homogenization process includes high-speed dispersing cutting.

9. The nanofiber aerogel composite material according to claim 8, characterized in that: The process parameters of the high-speed dispersive cutting include: a homogenous shearing speed of 100 to 20,000 rpm, and a homogenous shearing time of 10 to 120 min.

10. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S3, the temperature of the low-temperature freezing is -100~-30°C.

11. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S3, the low-temperature freezing time is 1 to 10 hours.

12. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S3, the vacuum drying time is 1 to 48 hours.

13. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S4, the mass fraction of the hydrophobic polymer in the hydrophobic polymer spinning solution is 1-20%.

14. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S4, the hydrophobic polymer is selected from at least one of polystyrene, polyvinylidene fluoride, fluorinated acrylic acid, fluorinated polyethylene and fluorinated polyurethane.

15. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S4, the second solvent is selected from at least one of dimethylformamide, dimethylacetamide, dichloromethane and methylpyrrolidone.

16. The nanofiber aerogel composite material according to claim 1, characterized in that: In step S4, the process parameters of the second electrospinning include: a voltage of 1 to 40 kV, a receiving distance of 10 to 50 cm, and a liquid supply rate of the spinning solution of 0.5 to 5 mL / h.

17. Use of the nanofiber aerogel composite material according to any one of claims 1 to 16 in the preparation of an evaporative cooling vest.

18. An evaporative cooling vest based on nanofiber aerogel, characterized in that: The fabric of the evaporative cooling vest comprises the nanofiber aerogel composite material as described in any one of claims 1 to 16.

Citation Information

Patent Citations

  • Ultra-light aerogel heat insulation material with waterproof and moisture permeation functions and preparation method thereof

    CN107097492A